Microfluidic systems for neuronal cell culture - Johnstone, Alex (2016)
At a high level of abstraction, the brain is a system for analysing sensory information, and responding appropriately. That information is encoded and stored in the millions of neural circuits that comprise the brain. Deciphering this code is essential to understanding how memories are implemented in physiologically normal brain tissue, and to inferring the nature of some neurological disorders affecting memory such as Alzheimer’s disease, in which the neural encoding is aberrant or unsuccessful. One approach to this problem is to reduce the complexity of the brain functionality to three elements: stimuli, response, and reinforcement. The electrical activity of individual neurons can be recorded with electrodes, capturing the pathways of signal propagation in a network of cells. Individual neurons can be also induced to reliably respond to electrical or optical stimuli, so that they initiate, relay, or even block a signal. If the stimuli to a finite network of cells can be made heterogeneous so that only a sub-population of cells is targeted, then the network can be trained to react in a repeatable way to a given stimulus, testing the concept that the higher order functions of the brain can emerge from a simple set of underlying computational rules. Training however requires a mechanism for reinforcing only some of the possible pathways, in synchrony with stimuli and in response to the recorded network activity. In the intact brain, this mechanism is pharmacological: a neuromodulator such as dopamine is released throughout the brain, but as it only coincides with some but not all neuronal activity, the reinforcement is temporally selective. The key task of this project is to emulate this selective neuromodulator reinforcement in vitro in a finite neuronal network. The project must also provide capacity for heterogeneous stimulation and individual cell recording, which can be coordinated with the reinforcement under computer control. The strategy used was to develop microscale chambers to house a small network of cultured neurons. The chambers were integrated with existing cell recording and stimulating technologies, so that specific connections between neurons could be both monitored and induced. Neuronal cultures of a few hundred cells were successfully grown in microchannels, on substrates capable of recording their electrical activity. Thus it was possible to create a small cultured network in which complete network activity could be detected, subject to a sufficiently precise recording technique. Additionally, a fluid-handling system was developed in order to emulate the continual replenishment of nutrients and soluble gases that are essential to cell survival. The system is intended to deliver soluble chemicals that modulate neuronal activity, on a timescale that is consistent with neuromodulator delivery in the body. The fluid handling system comprises a set of pressure driven pumps under automated computer control. This system has the capacity to deliver neuromodulator in solution with high spatiotemporal precision. The ability to reliably deliver and wash off precise volumes of drugs in a matter of seconds, with no dilution of the intended concentration, will be of great benefit to researchers investigating the response of various cell types to different agonists.